Antibacterial activity and cytocompatibility of an implant coating consisting of TiO2 nanotubes combined with a GL13K antimicrobial peptide - Li T (Dove Medical Press, 2017)
Tao Li,1,2 Na Wang,1 Su Chen,1 Ran Lu,1 Hongyi Li,2 Zhenting Zhang1 1Department of Prosthodontics, School of Stomatology, Capital Medical University, 2Key Laboratory of Advanced Functional Materials, School of Materials and Engineering, Beijing University of Technology. Beijing, People’s Republic of China Abstract: Prevention of implant-associated infections at an early stage of surgery is highly desirable for the long-term efficacy of implants in dentistry and orthopedics. Infection prophylaxis using conventional antibiotics is becoming less effective due to the development of bacteria resistant to multiple antibiotics. An ideal strategy to conquer bacterial infections is the local delivery of antibacterial agents. Therefore, antimicrobial peptide (AMP) eluting coatings on implant surfaces is a promising alternative. In this study, the feasibility of utilizing TiO2 nanotubes (TNTs), processed using anodization, as carriers to deliver a candidate AMP on titanium surfaces for the prevention of implant-associated infections is assessed. The broad-spectrum GL13K (GKIIKLKASLKLL-CONH2) AMP derived from human parotid secretory protein was selected and immobilized to TNTs using a simple soaking technique. Field emission scanning electron microscope, X-ray diffraction, Fourier transform infrared spectroscopy, and liquid chromatography–mass spectrometry analyses confirmed the successful immobilization of GL13K to anatase TNTs. The drug-loaded coatings demonstrated a sustained and slow drug release profile in vitro and eradicated the growth of Fusobacterium nucleatum and Porphyromonas gingivalis within 5 days of culture, as assessed by disk-diffusion assay. The GL13K-immobilized TNT (GL13K-TNT) coating demonstrated greater biocompatibility, compared with a coating produced by incubating TNTs with equimolar concentrations of metronidazole. GL13K-TNTs produced no observable cytotoxicity to preosteoblastic cells (MC3T3-E1). The coating may also have an immune regulatory effect, in support of rapid osseointegration around implants. Therefore, the combination of TNTs and AMP GL13K may achieve simultaneous antimicrobial and osteoconductive activities. Keywords: orthopedic infections, titanium, nanotubes, antimicrobial peptide